Classroom Management at the Secondary Level: How Does Teachers’ Confidence Vary According to Their Context? - Gaudreau, Nancy; Marchand, Mélanie; Nadeau, Marie-France (Apprendre et enseigner aujourd’hui)

(untitled) (Conseil pédagogique interdisciplinaire du Québec, 2026)
This article presents the key findings of a study conducted with 1,025 secondary school teachers regarding their classroom management self-efficacy (CMSE). The results reveal three major findings : qualifying teacher education (teaching certificate and degree attainment) plays a determining role in the development of CMSE ; professional experience exerts a progressive positive effect on all dimensions, particularly on the establishment of clear expectations ; and contextual factors significantly influence CMSE, notably employment status and teaching sector. These findings highlight the importance of providing differentiated support based on teachers’ experience level and teaching context.